The Representation of Adult Family Members in Selected Children's Books by Roald Dahl - Kerford, Justine (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2016)
This thesis focuses on the representation of the five adult family members (mothers, fathers, grandmothers, grandfathers and aunts) that are present in a specialised corpus of Roald Dahl's children's literature. Children's fiction provides insight into how society views childhood as it reflects the dominant ideologies in society (Larkin-Lieffers 2010).The family is "central to most children's literature" (Alston 2008: 2) which makes the analysis of the family in children's fiction important. Society favours particular representations of the family, as well as men and women, and these representations are also reflected in the fiction available to readers. I have used Critical Discourse Analysis and Corpus Linguistics in order to establish how adult family members are represented in Dahl's fiction. The physical description and the verbs of speech that collocate significantly with the different tagged characters are analysed to establish patterns in representation. Verbs of speech give the reader information that allows them to establish the emotion and attitude of the character and this helps the reader make judgements with regards to the positive or negative perception of the character. The repeated use of particular descriptions and verbs of speech primes the reader to associate particular features with certain characters and the evaluation provided by these features bleeds over onto the characters. There is evidence of a continuum of verbs of speech moving from verbs of speech with low pitch and low volume like 'said' to ones with a high pitch and high volume like 'shrieked'. The tagged characters are discussed according to the continuum to establish any patterns the verb of speech use. Women were found to collocate with verbs of speech like 'shrieked, 'screamed' and 'wailed' which suggests that women are more hysterically emotional while men collocate with verbs of speech like 'shouted' and 'yelled' which were less hysterical and suggest aggression. Aunts were the exception to this pattern as they collocated with more masculine verbs of speech, like 'shouted'. These patterns help establish whether or not the representations follow the dominant ideologies of women being emotional and home bound and men being aggressive and more active in the public sphere.
Keywords: Uncatalogued